Learning Theory Approaches in Developing Islamic Education Curriculum: Efforts to Realize Effective Islamic Learning - Andrini, Mike; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Paedagogie, 2025)
Abstract This study explores the application of learning theories, behaviorism, cognitivism, constructivism, and humanism, in the development of the Islamic Religious Education (PAI) curriculum as an effort to create an effective and meaningful Islamic learning process. Using a qualitative library research approach, this paper examines how these theories contribute to enhancing students’ motivation, understanding of religious values, and character formation. The findings indicate that behaviorism supports the cultivation of discipline and positive habits through reinforcement and habituation; cognitivism emphasizes structured thinking and rational understanding of Islamic teachings; constructivism encourages students to actively build knowledge through experience, discussion, and reflection; and humanism focuses on personal growth and self-actualization in harmony with spiritual and social development. Integrating these theories into the PAI curriculum promotes more contextual, student-centered, and value-oriented learning. However, implementation still faces several challenges, such as limited teacher understanding of modern learning approaches, insufficient learning resources, and an assessment system that prioritizes cognitive outcomes over holistic development. Therefore, teacher training, innovative pedagogy, and comprehensive evaluation are needed to optimize the application of learning theories in Islamic education.